Manajemen Laba, Profitabilitas, dan Likuiditas sebagai Peringkat Obligasi - Ulya Anisa’ul Maghfiroh; Fidiana Fidiana (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2019)
Bond rating is one of the considerations before investors to invest bonds. This is done because the bond rating provides an informative statement and gives a signal about the probability of a company's debt failure. In the process of rating bond ratings, rating agencies assess the company through the company's financial statements. The purpose of the assessment is to find out whether earnings management, profitability, and liquidity and their influence in the bond rating. The sample in this research is a manufacturing company which is listed in the Indonesia Stock Exchange (IDX) during the 2013-2016 period and rated by PT Pefindo. The sample that was selected using purposive sampling method to obtain the sample of 11 companies. Hypothesis testing uses logistic regression analysis to test the influence of earnings management, profitability, and liquidity to bond rating. The results of this research proves that the variable of earnings management and liquidity does not influenced the rating of bonds. While the profitability variables give influence the rating of bonds